Kawīniphon Lūang Čhakkrapānī (Rœ̄k) - Čhakkrapānī (Rœ̄k),Sirirat Thawīsap (Krom Sinlapākō̜n, 2021)
Thai poetry by Luang Chakkraprani (Roek), a prominent artist during the reigns of King Rama 3 and King Rama 4
Keywords: Biografie